Bacterial Cellulose-Based Metallic Green Nanocomposites for Biomedical and Pharmaceutical Applications - Badshah, Munair; Ullah, Hanif; Wahid, Fazli; Khan, Taous (Current Pharmaceutical Design, 2020)
Background: Bacterial cellulose (BC) is a microbial biosynthesized polymer having exceptional physical and mechanical features as compared to plants derived cellulose. BC has a wide range of applications such as traditional dessert as well as gelling, stabilizing and thickening agent in many foods. The more unconventional applications of BC include but not limited to enzymes immobilization, tissue engineering, artificial blood vessels and heart valve prosthesis, bone and cartilage regeneration, corneal replacement, skin tissues repair and dental root canal treatment. Objective: This review presents the applications of BC expanded by preparing its nanocomposites with drugs, fibres, metals and metallic oxides. These nanocomposites have been studied for applications in drug delivery and biosensors. Methods: The current review focuses on the potential applications of BC-based green metallic and metal-based inorganic nanocomposites as wound dressing material, a tool for microbial control, cardiovascular stenting, and as bone tissue engineering material. In addition, the potential pharmaceutical applications of BC-based green metallic nanocomposites have also been discussed. Results: The reported BC-based nanocomposites owe advantages in terms of stability, environment friendliness and cost-effectiveness, prolonged therapeutic effects and biocompatibility with body tissues, with faster wound healing and negligible cytotoxicity. Conclusion: The current review provides a deep insight into the assessment of such nanocomposites in terms of useful applications and potential commercialization for pharmaceutical as well biomedical purposes.
Keywords: metallic nanocomposites